Implementation Of Risk Management And Restructuring In Minimising Non-Performing Loans Pt Mandiri Tunas Finance - Afiza Afiza; Pipit Buana Sari (Utan Kayu Publishing, 2025)
This study aims to determine the factors that influence non-performing loans at PT. Mandiri Tunas Finance, the implementation of Risk Management in minimizing non-performing loans at PT. Mandiri Tunas Finance and restructuring carried out in overcoming non-performing loans. The research method uses descriptive qualitative research. The results of the study indicate that the factors that influence non-performing loans at PT. Mandiri Tunas Finance are divided into two factors, namely internal factors such as incorrect analysis and the Account Officer's lack of accuracy in analyzing 5C both before the loan is taken and after it is disbursed, while external factors such as uncertain economic conditions have caused customers' businesses to experience reduced income and can no longer pay. The implementation of Risk Management in minimizing non-performing loans at PT. Mandiri Tunas Finance, including: Carrying out financing settlements politely and persuasively with customers; Carrying out rescheduling , namely changing the payment schedule for customer obligations or their terms; Carrying out reconditioning , namely changing some or all of the financing requirements without increasing the remaining principal of the customer's obligations that must be paid to the bank; Restructuring , namely changing the financing requirements. Restructuring in overcoming problematic credit at PT. Mandiri Tunas Finance is carried out by prioritizing the element of wisdom regarding the situation faced by debtors and the debtor's ability to pay, including taking into account the direction and policies of the regulator.